A novel two‐component system modulates quorum sensing and pathogenicity in Burkholderia cenocepacia. Issue 1 (9th February 2018) - Cui, Chaoyu; Yang, Chunxi; Song, Shihao; Fu, Shuna; Sun, Xiuyun; Yang, Liang; He, Fei; Zhang, Lian‐Hui; Zhang, Yongliang; Deng, Yinyue
Summary: Quorum sensing (QS) is widely utilized by bacterial pathogens to regulate biological functions and pathogenicity. Recent evidence has shown that QS is subject to regulatory cascades, especially two‐component systems that often respond to environmental stimulation. At least two different types of QS systems regulate pathogenesis in Burkholderia cenocepacia . However, it remains unclear how this bacterial pathogen controls these QS systems. Here, we demonstrate a novel two‐component system RqpSR (R egulatingQ uorum sensing andP athogenicity), which plays an important role in modulating QS and pathogenesis in B. cenocepacia . We demonstrate strong protein‐protein binding affinity between RqpS and RqpR. Mutations in rqpS and rqpR exerted overlapping effects on B. cenocepacia transcriptomes and phenotypes, including motility, biofilm formation and virulence. In trans expression of rqpR rescued the defective phenotypes in the rqpS mutant. RqpR controls target gene expression by direct binding to DNA promoters, including the cis ‐2‐dodecenoic acid (BDSF) and N ‐acylhomoserine lactone (AHL) signal synthase gene promoters. These findings suggest that the RqpSR system strongly modulates physiology by forming a complicated hierarchy with QS systems. This type of two‐component system appears to be widely distributed and coexists with the BDSF QS system in various bacterial species. Abstract : In this study, a genome‐wide transposon mutagenesis was used to identify two‐component systems which regulate quorum‐sensing systems in the opportunistic pathogen Burkholderia cenocepacia . We have identified and characterized a novel two‐component system, RqpS‐RqpR, that modulates QS systems and biological functions including motility, biofilm formation and virulence in B. cenocepacia .